The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2304/elea.2014.11.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Reflection as an Indicator of Cognitive Presence

Abstract: In the Community of Inquiry (CoI) model, cognitive presence indicators can be used to evaluate the quality of inquiry in a discussion forum. Engagement in critical thinking and deep knowledge can occur through reflective processes. When learners move through the four phases of cognitive presence (triggering, exploration, integration, resolution), the processes of discussion and reflection are important in developing deep understanding. In this article, data from the online discussion archives within a blended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 23 publications
(36 reference statements)
4
32
0
2
Order By: Relevance
“…The PIM includes four phases: (1) a triggering event, where a problem is identified for further inquiry; (2) exploration, where an individual explores the issue; (3) integration, where learners concept meaning from ideas formed in the exploration phase; and (4) resolution, where students can apply the new skills and knowledge learned from the previous phases into real-world application(s) (Garrison et al, 2000). Reflection is a key aspect of the CoI framework and helps learners to increase their cognitive presence as Redmond (2014) states, "reflecting on learning content and outcomes relates to knowledge acquisition where learners identify their increased knowledge and skills in the subject area" (p. 50). Garrison, 2007, Journal of Asynchronous Learning Networks, 11, p. 63.…”
Section: Cognitive Presencementioning
confidence: 99%
“…The PIM includes four phases: (1) a triggering event, where a problem is identified for further inquiry; (2) exploration, where an individual explores the issue; (3) integration, where learners concept meaning from ideas formed in the exploration phase; and (4) resolution, where students can apply the new skills and knowledge learned from the previous phases into real-world application(s) (Garrison et al, 2000). Reflection is a key aspect of the CoI framework and helps learners to increase their cognitive presence as Redmond (2014) states, "reflecting on learning content and outcomes relates to knowledge acquisition where learners identify their increased knowledge and skills in the subject area" (p. 50). Garrison, 2007, Journal of Asynchronous Learning Networks, 11, p. 63.…”
Section: Cognitive Presencementioning
confidence: 99%
“…Therefore, the design and context of the discussion activities were of paramount importance for the improvement seen in students' cognitive presence. It was noted in a few recent studies (e.g., Redmond, 2014) that when online discussions were structured appropriately, students could share and document their own thinking and reflect on both their own and other students' contributions. When asked to reflect on their learning experience with a given scenario, students could apply their new knowledge more easily and resolve the issue, which means they could reach the resolution phase.…”
Section: Cognitive Presencementioning
confidence: 99%
“…Dewey assumed that minds-on experiences and activities are needed. Various instructional approaches, such as problem-solving, exploration, inquiry, and asking for high-level questions, can develop pre-service teachers' critical thinking ability (Redmond, 2014). Prayogi & Asy'ari (2013) previously conducted research and found that pre-service teachers' critical thinking ability could be developed and improved through experimental activities in the laboratory to solve problems.…”
Section: Introductionmentioning
confidence: 99%